Icons, Liturgy, Saints: Ecological insights from Orthodox spirituality - Chryssavgis, John (International review of mission, 2010)
The technical language and specific images that we adopt when we speak about preservation of the natural environment depend on values and images that we promote and even presume in our daily behaviour and lifestyle. In Orthodox Christian spirituality, such language and images certainly play a crucial role. This presentation considers the central importance of: 1) the world of icons as the way we view and perceive creation; 2) the beauty of liturgy as the way we celebrate and respond to creation; and 3) asceticism in the lives of the saints as the way we respect and treat creation. It draws on classic Orthodox Christian texts as well as contemporary literature to provide fundamental spiritual insights into the way we comprehend God's creation and the way we should confront its exploitation in modern times.